From contents to comments: Social TV and perceived pluralism in political talk shows. (February 2018) - Ceron, Andrea; Splendore, Sergio
Going beyond source and content pluralism, we propose a two-dimensional audience-based measure of perceived pluralism by exploiting the practice of "social TV". For this purpose, 135, 228 tweets related to 30 episodes of prime time political talk shows broadcast in Italy in 2014 have been analyzed through supervised sentiment analysis. The findings suggest that the two main TV networks compete by addressing generalist audiences. The public television offers a plural set of talk shows but ignores the anti-political audience. The ideological background of the anchorman shapes the audience's perception, while the gender of the guests does not seem to matter.